Self-rated health as a predictor of outcomes of type 2 diabetes patient education programmes in Denmark. (October 2016) - Laursen, D.H.; Christensen, K.B.; Christensen, U.; Frølich, A.
Abstract: Objective: To explore if self-rated health (SRH) can predict differences in outcomes of patient education programmes among patients with type 2 diabetes over time. Study design: This is an observational cohort study conducted among 83 patients with type 2 diabetes participating in patient education programmes in the Capital Region of Denmark. Methods: Questionnaire data were collected by telephone interview at baseline and 2 weeks (77 participants, 93%) and 12 months (66, 80%) after the patient education ended. The seven-scale Health Education Impact Questionnaire (HeiQ) was the primary outcome. The independent variable was SRH, which was dichotomized into optimal or poor SRH. Changes over time were assessed using mean values and standard deviation (SD) at each time point and Cohen effect sizes. Odds ratios and 95% confidence intervals were calculated for the likelihood of having poor SRH for each baseline sociodemographic and health-related variable. Results: Twelve months after patient education programmes, 60 (72%) patients with optimal SRH at baseline demonstrated increased self-management skills, overall acceptance of chronic illness, positive social interaction with others, and improved emotional well-being. Participants with poor SRH (23, 28%) reported no improvements over time. Not being married (odds ratio [OR] 7.79, P < 0.001), living alone (OR 4.93, P = 0.003), having hypertension (OR 8.00, P = 0.031), and being severely obese (OR 4.07, P = 0.009) were significantly associated with having poor SRH. After adjusting for sex, age and vocational training, marital status (OR 9.35, P < 0.001), cohabitation status (OR = 4.96, P = 0.005) and hypertension (OR 10.9, P = 0.03) remained associated with poor SRH. Conclusions: We found a strong association between SRH and outcomes of patient education, as measured by the HeiQ, at 12 months. Only participants with optimal SRH appeared to benefit from patient education. Other patient characteristics may be responsible to explain the observed difference between patients with optimal and poor SRH. Highlights: Long-term effect of patient education was measured using HeiQ. Diabetes patients with optimal self-rated health benefit from patient education. No improvements in outcome among patients with poor self-rated health. Patient education may not be equally suitable for all diabetes participants.